2016
DOI: 10.1002/cphc.201600706
|View full text |Cite
|
Sign up to set email alerts
|

Monomer Dynamics of Alzheimer Peptides and Kinetic Control of Early Aggregation in Alzheimer's Disease

Abstract: The rate of reconfiguration—or intramolecular diffusion—of monomeric Alzheimer (Aβ) peptides is measured and, under conditions that aggregation is more likely, peptide diffusion slows down significantly, which allows bimolecular associations to be initiated. By using the method of Trp–Cys contact quenching, the rate of reconfiguration is observed to be about five times faster for Aβ40, which aggregates slowly, than that for Aβ42, which aggregates quickly. Furthermore, the rate of reconfiguration for Aβ42 speed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 50 publications
1
26
0
Order By: Relevance
“…Acharya et al (81) have recently investigated the chain dynamics of Ab by monitoring quenching of the triplet state of tryptophan by cysteine. The inferred timescale of the contact formation between residue 4 and residue 35 was several microseconds.…”
Section: Fret Efficiency-lifetime Analysis and Nsfcs Reveal Nanosementioning
confidence: 99%
“…Acharya et al (81) have recently investigated the chain dynamics of Ab by monitoring quenching of the triplet state of tryptophan by cysteine. The inferred timescale of the contact formation between residue 4 and residue 35 was several microseconds.…”
Section: Fret Efficiency-lifetime Analysis and Nsfcs Reveal Nanosementioning
confidence: 99%
“…From a FRET study of Aβ40 and Aβ42 it was found that both peptides do not exhibit conformational dynamics exceeding 1 µs, 35 which also agrees with the findings from fluorescence measurements using the method of Trp-Cys contact quenching. 36 Given the simulation length of 30 µs of the MD data generated by D. E. Shaw Research, we use their data (which were kindly provided by them) to assess the kinetics of Aβ40 as sampled by the different FFs.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies of different unfolded proteins have revealed a wide range of diffusion coefficients depending on sequence, pH and other solvent conditions [511]. For example, the intramolecular diffusion coefficient of the Alzheimer’s peptide lacking residues 41 and 42 (Aβ40) was five times faster than the Alzheimer’s peptide containing those residues (Aβ42) [12]. This 5-fold change in intramolecular diffusion rate correlates with the difference in lag time of aggregation for Aβ40 vs. Aβ42, which suggests that aggregation is kinetically controlled by the reconfiguration of the monomer.…”
Section: Introductionmentioning
confidence: 99%